Innovative Digital Commerce and Its Impact on Doom Spending and Unsustainable Fashion Choices Among Generation Z: A TikTok Live Shopping Study - Gracias Irene Jarut; Selvi Ana (COMMENTATE: Journal of Communication Management, 2025)
This study examines the effect of TikTok Live Shopping on doom spending and its impact on unsustainable fashion choices among Generation Z consumers. Using a quantitative survey method, data were collected from 150 respondents aged 18–26 who actively use TikTok and have engaged with its live shopping feature. The results show that TikTok Live Shopping has a significant positive effect on doom spending (β = 0.571, p < 0.001), and doom spending significantly influences unsustainable fashion choices (β = 0.507, p < 0.001). TikTok Live Shopping also directly affects unsustainable fashion choices (β = 0.355, p < 0.001). Furthermore, the mediation analysis indicates that doom spending partially mediates the relationship between TikTok Live Shopping and unsustainable fashion choices, with the indirect effect also being significant. All four hypotheses (H1–H4) were supported, demonstrating that real-time purchasing features on social commerce platforms foster impulsive buying behavior, which in turn drives less sustainable fashion consumption. These findings provide valuable insights for marketers and policymakers in promoting responsible consumption and developing ethical marketing strategies in the era of digital commerce.